Unraveling Role Ambiguity and Work Loyalty: The Moderating Impact of Employee Motivation on Performance - Andreansyah, Adre Septian; Sumampouw, Ruland Willy Jack (Human Capital and Organizations, 2025)
In the New Student Admission System for the 2025/2026 academic year, age is no longer a priority for entering public high schools; instead, grades are the primary focus. Every student, regardless of age, has an equal opportunity. With this change, students must maintain good academic grades to compete. State High School 13 Jakarta is an institution desired by many parents. The domicile pathway for entry to State High School 13 Jakarta offers the most opportunities, with 124 students out of a total capacity of 365 students. The domicile pathway to enter State High School requires high grades, so students are required to have exemplary academic achievements. The purpose of this study was to identify the impact of learning interest and learning motivation on learning outcomes. This study involved 102 randomly selected respondents from parents at State High School 13 Jakarta, utilizing quantitative research methods. Data collection was carried out by filling out a questionnaire using a Likert scale. The data analysis method used was IBM SPSS 27 and the Structural Equation Modeling SmartPLS 3.0 approach. The results of this study indicate that learning interest and learning motivation have a positive and significant influence on learning achievement.